The Wounds Behind the Numbers: A Phenomenological Study of Men's Experiences in Facing Bride Price Pressure from a Social Accounting Perspective - Rahmat Hidayatullah; Nasruddin Nasruddin; Nur Asia; Darwis Darwis; Arifuddin Arifuddin (CV Edujavare Publishing, 2026)
Uang panai is a Bugis-Makassar customary practice that has increasingly transformed into a significant financial burden for men seeking marriage. This study aims to explore the lived experience of men facing uang panai pressure through the lens of social accounting. A qualitative phenomenological approach using Interpretative Phenomenological Analysis (IPA) was employed to analyze in-depth interview data from nine male informants in South Sulawesi. Four main themes emerged: (1) uang panai as a social accountability burden exceeding economic capacity; (2) psychological pressure and masculinity identity crisis; (3) negotiation and resistance strategies; and (4) redefinition of uang panai meaning within contemporary social accounting frameworks. Findings affirm that uang panai has shifted from a symbolic-cultural function to a financially-based social control mechanism creating deep psychological wounds, while urging value reconstruction of customary practices.